Retração de geleiras na Antártica Marítima promove mudanças bioquímicas da matéria orgânica do solo e altera as comunidades microbianas - Silva, Neilson Rocha da (2023)
In recent decades, Antarctica has undergone significant glacier retreats, exposing rocks andpromoting soil development. Understanding soil organic matter (SOM) dynamics, its biochemicalcomposition, and microbial communities in ice-free areas is limited, especially regarding theeffects of glacier retreats and soil drainage. This study aimed to (i) review the effects of globalwarming on SOM dynamics in the Antarctic Peninsula and Maritime Antarctica and (ii) analyzechanges in SOM biochemical composition and soil microbial communities in glacier retreat areasof Maritime Antarctica under different environments and vegetation cover. The study conducted areview and compilation of SOM dynamics information for the first objective, while the secondobjective involved collecting soil and vegetation samples for physical and chemical analyses ofsoil, SOM biochemical composition, and microbial communities. Sample collections were madeat sites determined by dominant geomorphological processes and vegetation cover, forming aglacier-coast marine transect with varying glacier distances. Soil < 2 mm was fractionated intoparticulate organic matter (POM) and mineral-associated organic matter (MAM) for carbon (C),nitrogen (N), and biochemical composition determination. Organic C levels were determined usingthe Walkey Black method, total N with the Kjeldahl method, and organic molecules were extractedthrough thermochemolysis. Microbial community characterization was performed by extractingand analyzing phospholipid fatty acids (PLFA). Results revealed that stabilized soil influencedplant colonization, leading to changes in SOM biochemical composition and microbialcommunities, particularly in the surface soil, with an impact on fungi. However, changes in SOMbiochemical composition and microbial communities associated with glacier retreats did notsignificantly affect C and N levels in both MAM and POM. MAM showed changes frommicrobial-origin organic matter (abundant in lipids) near glaciers to plant-origin organic matter(higher aromaticity and abundance of carbohydrates, terpenes, and biopolymers) further fromglaciers, with up to an 80% reduction in lipids, for instance. These findings highlighted the crucialrole of cryptogamic and cryoendolithic communities in altering the molecular composition ofSOM. The PLFA analysis indicated a shift from a bacterial-dominated to a fungal-dominateddomain with glacier retreats. The increased presence of fungi reached 66%, possibly linked tocryoendolithic occupation in sites further from glaciers, where the dominant presence of lichenscorrelated with total nitrogen levels and soluble organic matter (SOM), terpenes, andcarbohydrates fractions. In conclusion, well-drained and stabilized soils in Maritime Antarcticaled to an increase in surface soil fungal communities in sites further from glaciers, along with anincrease in terpenes and carbohydrates produced by plants. In the subsurface soil, data compilationidentified the 10-15 cm depth as the microhabitat providing the best environmental conditions andresources for microbial communities.